CGIAR Evaluation Framework and Policy 2022 Brief - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2022)
A two-pager condensing the main elements and scope included in the recently approved CGIAR Evaluation Framework and Policy.